Bioinformatic analysis of the LCN2–SLC22A17–MMP9 network in cancer: The role of DNA methylation in the modulation of tumor microenvironment - Candido, Saverio; Tomasello, Barbara; Lavoro, Alessandro; Falzone, Luca; Gattuso, Giuseppe; Russo, Angela; Paratore, Sabrina; McCubrey, James A.; Libra, Massimo (Frontiers in Cell and Developmental Biology, 2022)
Several features of cancer cells such as proliferation, invasion, metastatic spreading, and drug resistance are affected by their interaction with several tumor microenvironment (TME) components including Neutrophil Gelatinase-Associated Lipocalin (NGAL), Solute carrier family 22 member 17 (SLC22A17), and Matrix Metallopeptidase 9 (MMP-9). These molecules play a key role in tumor growth, invasion, and iron-dependent metabolism of cancer cells. However, the precise epigenetic mechanisms underlying the gene regulation of Lipocalin 2 (LCN2), SLC22A17, and MMP9 in cancer remain still unclear. To this purpose, computational analysis was performed on TCGA and GTEx datasets to evaluate the expression and DNA methylation status of LCN2, SLC22A17, and MMP9 genes in different tumor types. Correlation analysis between gene/isoforms expression and DNA methylation levels of LCN2, SLC22A17, and MMP9 was performed to investigate the role of DNA methylation in the modulation of these genes. Protein network analysis was carried out using Reverse Phase Protein Arrays (RPPA) data to identify protein-protein interactions of LCN2-SLC22A17-MMP9 network. Furthermore, survival analysis was performed according to gene expression and DNA methylation levels. Our results demonstrated that LCN2 and MMP9 were mainly upregulated in most tumor types whereas SLC22A17 was largely downregulated representing a specific hallmark signature for all gastrointestinal tumors. Notably, the expression of LCN2, SLC22A17, and MMP9 genes was negatively affected by promoter methylation. Conversely, intragenic hypermethylation was associated to overexpression of SLC22A17 as well as MMP9 gene. Protein network analysis highlighted the role of LCN2-SLC22A17-MMP9 network in TME by the interaction with Fibronectin 1 and Claudin 7 especially in rectal tumor. Moreover, the impact of expression and methylation status of LCN2, SLC22A17, and MMP9 on overall survival and progression free interval was tumor type- dependent. Overall, our analyses provide a detailed overview of expression and methylation status of LCN2, SLC22A17, and MMP9 in all TCGA tumors indicating that the LCN2-SLC22A17-MMP9 network was strictly regulated by DNA methylation within TME. Our findings pave the way for the identification of novel DNA methylation hotspots with diagnostic and prognostic values and suitable for epi-drug targeting.